2016
DOI: 10.1016/j.jbusres.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Customer commitment to luxury brands: Antecedents and consequences

Abstract: The intensifying competition in the luxury sector necessitates the need for managers to identify the factors underpinning customers' commitment to a luxury brand. Understanding commitment not only provides an insight into the question, how customers commit, but also uncovers why customers commit to a particular brand. Using a questionnaire-based survey with customers, this research examines the antecedents and consequences of customer commitment to luxury brands. The findings indicate the differential influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
140
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 52 publications
14
140
0
13
Order By: Relevance
“…It was also found that trust holds a significant relationship with commitment in various service-related contexts as well as in a luxury brand context (Moreira and Silva, 2015;Ou et al, 2011;Sumaedi, Juniarti and Bakti, 2015;Shukla et al, 2016). Therefore, the two relationship quality factors, trust and commitment, are hypothesised to have significant relationships with each other while trust also has a significant relationship with the behavioural intention of customers in relation to postpurchase service and repairs at a luxury motor vehicle dealership.…”
Section: The Relationships Between Trust Commitment and Behavioural mentioning
confidence: 94%
See 1 more Smart Citation
“…It was also found that trust holds a significant relationship with commitment in various service-related contexts as well as in a luxury brand context (Moreira and Silva, 2015;Ou et al, 2011;Sumaedi, Juniarti and Bakti, 2015;Shukla et al, 2016). Therefore, the two relationship quality factors, trust and commitment, are hypothesised to have significant relationships with each other while trust also has a significant relationship with the behavioural intention of customers in relation to postpurchase service and repairs at a luxury motor vehicle dealership.…”
Section: The Relationships Between Trust Commitment and Behavioural mentioning
confidence: 94%
“…Commitment has also been found to be significantly related to behaviour intention and, with respect to its different categories as proposed by Parasuraman et al (1994), to different service, retail and luxury brand contexts (Fullerton, 2014;Jani and Han, 2011;Liang and Wang, 2007;Moreira and Silva, 2015;Shukla, Banerjee and Singh, 2016). Therefore, two relationship quality factors -customer satisfaction and commitment -are hypothesised to have significant relationships with each other and the behavioural intention of customers when post-purchase service and repairs at a luxury motor vehicle dealership are considered.…”
Section: The Relationships Between Customer Satisfaction Commitment mentioning
confidence: 95%
“…Inclusive, os autores sugerem que futuros estudos utilizem a marca como moderadora na relação entre comprometimento afetivo, normativo e intenção de recompra. Desse modo, a marca pode assumir um importante papel moderador na relação entre o comprometimento e o comportamento de repetição de compras (Shukla et al, 2016). Vale salientar que diferentes marcas podem impactar de forma distinta a relação entre o comprometimento afetivo e o comprometimento normativo e, também, a intenção de recompra do consumidor.…”
Section: O Papel Moderador E Mediador Da Marcaunclassified
“…No entanto, podemos identificar que a primeira hipótese proposta H1, a qual propõe que o comprometimento afetivo (COMP_AFE) esta positivamente associado a satisfação do cliente (SAT), foi sustentada pelos resultados. Para a presente relação, o coeficiente padronizado encontrado foi de 0, 914 e t-value= 9,426, sendo que esta relação também foi evidenciada em estudos anteriores (MATHIEU, 1991;SHUKLA;BANERJEE;SINGH. 2016).…”
Section: Fonte: Elaborada Pelos Autoresunclassified
“…Observa-se que no contexto analisado, o comprometimento calculativo não seja susceptível em desenvolver uma forte ligação com a satisfação do cliente (aluno), pelo fato do comprometimento calculativo aproximar o aluno a IES, pela percepção dos custos de deixar o relacionamento existente (GUSTAFSSON;ROOS, 2005;SHUKLA;BANERJEE;SINGH, 2016). A hipótese H3 que indica que a satisfação do cliente (SAT) é impactada positivamente pelo comprometimento normativo (COMP_NORM), foi corroborada, apresentando coeficiente padronizado= 0,218 e t-value= 3,470.…”
Section: Fonte: Elaborada Pelos Autoresunclassified